Combination atezolizumab, bevacizumab, pemetrexed and carboplatin for metastatic EGFR mutated NSCLC after TKI failure. (September 2021) - Lam, T.C.; Tsang, K.C.; Choi, H.C.; Lee, V.H.; Lam, K.O.; Chiang, C.L.; So, T.H.; Chan, W.W.; Nyaw, S.F.; Lim, F.; Lau, J.O.; Chik, J.; et al.
Highlights: Pemetrexed-carbo plus bevacizumab and atezolizumab was effective in EGFR mutated lung cancer. Median PFS of 9.4 months, 1 year OS 72.5% in this heavily pretreated population were remarkable. Having similar efficacy, this regimen gave less toxicity compared with IMPower150 regimen. QoL was well preserved in patients which used pemetrexed as chemotherapy backbone. Post-trial rechallenge with EGFR TKI was effective with median PFS 4–6 months. Abstract: Introduction: Acquired resistance to TKI is an important unmet need in the management of EGFR mutated lung cancer. Recent clinical trial IMPower150 suggested that combination approach with VEGF inhibitor, check point inhibitor immunotherapy and platinum-based chemotherapy was effective in oncogene driven lung cancer. The current trial examined the efficacy of a modified regimen in an EGFR mutated cohort. Methods: An open-labelled, single arm, phase II study was conducted in patients with EGFR mutated NSCLC who had progressed on at least one EGFR TKI. For those with T790M mutation, radiological progression on osimertinib was required for enrolment. Patients were treated with combination atezolizumab (1200 mg), bevacizumab (7.5 mg/kg), pemetrexed (500 mg/m2) and carboplatin (AUC 5) given once every 3 weeks until progression. Results: Forty patients were enrolled. Median age was 62 (range 45–76) years. More than one half (23/40, 57.5%) had progressed on osimertinib. PD-L1 expression was < 1% in 52.5%. Median follow-up time was 17.8 months. ORR was 62.5%. Median PFS was 9.4 months (95% CI: 7.6 – 12.1). One year OS was 72.5% (95% CI: 0.56–0.83). Treatment related grade 3 or above adverse events (AE) occurred in 37.5% (15/40). Immune-related AE occurred in 32.5% (13/40) patients. Quality of life measures of function and symptoms did not change significantly throughout the course of treatments. Post-trial rechallenge with EGFR TKI containing regimen resulted in PFS of 5.8 months (95% CI 3.9–10.0 months). Conclusion: Combination approach of atezolizumab, bevacizumab, pemetrexed and carboplatin achieved promising efficacy in metastatic EGFR mutated NSCLC after TKI failure. The results were comparable with taxane based regimen of IMPower150 while toxicity profile was improved.